2019 IEEE PES Innovative Smart Grid Technologies Europe (ISGT-Europe) 2019
DOI: 10.1109/isgteurope.2019.8905437
|View full text |Cite
|
Sign up to set email alerts
|

Loss Performance Evaluation of Ferrite-Cored Wireless Power System with Conductive and Magnetic Shields

Abstract: This paper presents a loss evaluation of ferrite-cored wireless power transfer (WPT) systems using conductive and magnetic shield materials. The modelling and analyses of the coil systems were implemented using the finite element method. Three coil systems were modelled-circular coils, rectangular coils and flux-pipe coil system using magnetic shields (Mumetal and electrical steel) and conductive shields (aluminium and copper). From the results presented in the analyses, it was noted that ohmic losses and core… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The coupling coil design consideration is the most important due to its significant factors in the WPT system. To improve the efficiency of the coupling coil some studies have suggested to add magnetic shielding as a core material as shown in [3]- [6].…”
Section: Introductionmentioning
confidence: 99%
“…The coupling coil design consideration is the most important due to its significant factors in the WPT system. To improve the efficiency of the coupling coil some studies have suggested to add magnetic shielding as a core material as shown in [3]- [6].…”
Section: Introductionmentioning
confidence: 99%
“…The primary issue with WPT is power losses, therefore the convenience of not using wires comes at a price. While conduction loss in a conventional copper cable connection is not negligible, losses in WPT are significantly more [15], [16]. A large amount of alternating current is required to generate a magnetic field strong enough to link two separated coils.…”
mentioning
confidence: 99%